Task-dependent workload adjustment of female breeders in a cooperatively breeding fish. (4th December 2017) - Tanaka, Hirokazu; Frommen, Joachim G; Engqvist, Leif; Kohda, Masanori
Abstract : Helpers in cooperative breeders support the dominants in raising offspring. Such support is expected to be task dependent and to increase breeders' current or future reproductive success. We show that breeder females adjust their workload depending on the task in a cooperatively breeding fish by reducing their territory defense and broodcare according to the received help. However, they consistently showed the same amount of territory maintenance, indicating both load-lightening and additive effects taking place. Abstract: Parental investment affects the future survival and reproductive success of breeders. Therefore, breeders should optimize the amount of care they invest into the current offspring. In cooperative breeding systems, the amount of breeders' parental care is influenced by the behavior of brood-care helpers. Such workload adjustment is expected to depend on the task that needs to be fulfilled. While investment rules of breeders in respect to single tasks are well investigated in many bird and mammal species, little is known about behavioral adjustment of breeders when dealing with multiple tasks. Here, we examined the workload adjustment in multiple tasks of female breeders in the cooperatively breeding fish Neolamprologus obscurus . By combining behavioral observations with helper removal experiments in a wild population, we show that female territory defense and offspring care significantly decreased with increasing helper number. Furthermore, the workload invested in these tasks significantly increased after the removal of a helper, suggesting load-lightening effects in territory defense and offspring care. On the other hand, female territory maintenance behavior (i.e., excavating sand from the breeding shelter) did not correlate with helper number. While sand excavation significantly increased after the helper removal experiment, the size of the excavated stone area decreased after the helper removal in the recent study, suggesting that sand excavation may have additive effects for the breeders. These results demonstrate and underline the importance of task-dependent workload adjustment in cooperative breeders.